Perilaku Remaja Masjid X dalam Menyikapi Hoax di Media Sosial - Sri Mulyaningsih; Indra Wahyudi; Dewi Handayani Harahap (Jurnal Psikologi, 2020)
In recent 4 years, Indonesiantries to decrease the spreading of hoax news in social medias. The government has been trying various measures for instances: holding information session for public, setting some sign boards in intersections with notes like '' FIGHT FOR HOAX" or any similar notes, and even creating account in some social medias as a tool to clarify the hoax news which is spreading online.These measures give some positive results, proven by society's attitude towards hoax starts to change. They become moreunderstand about hoax and more open in accepting the truth of hoax news which once they believed. This change of attitude also can be seen on teenagers. According to data from Asosiasi Pengguna Jasa Internet Indonesia (Indonesian Internet Users Association), in 2017, 49.52% of internet users in Indonesia were teenagers. These numbers rise the possibility that most of hoax news are received and read mostly by teenagers.The researcher chose Nurhawwin Youth Squad as the subject ofresearch to study about their attitude towards hoax. The reason on choosing them as subject was because the researcher had observed them and found that the Nurhawwin Youth Squad has a forum to discuss about the latest news, including hoax, whichis held once a week. Through this forum, the researcher observes and studies about Nurhawwin Youth Squad's attitude towards hoax.This research paper uses qualitative method with 4 samples or informants. The methods used for collecting the data are interview and observation. The validity of the data is based on method proposed by Moleong (2015), which are credibility, transferability, dependability, and confirmability.The result of this research shows that NurhawwinMosque Youth Squad shows negative attitude towards hoax. They tend to ignore and and do not spread hoax news thoughtlessly. They take negative attitude when the information they got does not suit their rationality. However, there is an informant who shows positive attitude although it is only for twice times. After knowing truth and after understanding more about that matters through trustworthy mediaand person, They becomes indifferent towardstowards hoax.